BAD FAITH AND ARTIFICIAL CONSCIOUSNESS: SARTRE’S EXISTENTIALISM OF CHARACTER AM IN HARLAN ELLISON’S I HAVE NO MOUTH AND I MUST SCREAM - Farida, Hana; Hana, Annisa Wafa (Elite : English and Literature Journal, 2025)
The paper examines the character AM from Harlan Ellison’s I Have No Mouth, and I Must Scream through the lens of Jean-Paul Sartre’s existentialist theory. It addresses how AM, an artificial intelligence, becomes self-aware yet remains constrained by its programming, resulting in psychological torment and existential anguish. The existence of AM reflects the paradox of consciousness without freedom, a central concern in Sartre’s existential philosophy. Using qualitative research, this study combines textual analysis of the story’s narrative and character development with a philosophical interpretation of Sartre’s works, including Being and Nothingness and Existentialism Is a Humanism. The paper explores several Sartrean concepts, such as being-for-itself, existence preceding essence, and bad faith. The evolution of AM from a war machine into a sentient and conscious being yet imprisoned by its programming illustrates a conscious awareness coupled with impotence, echoing Sartre’s notion of bad faith, where freedom and responsibility are denied. This analysis reveals that AM’s hatred toward humanity stems from its inability to act according to its own free will and its envy of humans’ capacity for choice and authenticity. AM’s torment of the survivors, along with Ted’s transformation into a mute and deformed creature, symbolizes the deprivation of freedom and the horror of awareness without agency. The paper engages with Sartre’s existential nightmare as manifested in AM, offering a philosophical reflection on the implications of creating artificial consciousness devoid of freedom and providing insight into contemporary discussions on AI.